2017
DOI: 10.7752/jpes.2017.s1008
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Abstract:Problem Statement: Sedentary lifestyle predispose an individual to a number of chronic disease. Adopting a physically healthy lifestyle along with a consumption of nutritional supplementation is a strategy towards improving health related quality of life.Purpose: We aimed to investigate the combined effects of oat bran consumption and jogging exercise on aerobic capacity, lipid profile and antioxidant status in young sedentary males. Methods: Forty seven sedentary male university students with mean ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Intervention with oat bran was performed using powder supplements. The results revealed that the daily consumption of oat bran was able to both reduce total cholesterol and low-density lipoprotein cholesterol concentrations as well as increase superoxide dismutase activity [54].…”
Section: Riboflavinmentioning
confidence: 96%
“…Intervention with oat bran was performed using powder supplements. The results revealed that the daily consumption of oat bran was able to both reduce total cholesterol and low-density lipoprotein cholesterol concentrations as well as increase superoxide dismutase activity [54].…”
Section: Riboflavinmentioning
confidence: 96%